2018
DOI: 10.1101/283325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New strains for tissue-specific RNAi studies in Caenorhabditis elegans

Abstract: RNA interference is a powerful tool for dissecting gene function. In Caenorhabditis elegans, ingestion of double stranded RNA causes strong, systemic knockdown of target genes. Further insight into gene function can be revealed by tissue-specific RNAi techniques. Currently available tissue-specific C. elegans strains rely on rescue of RNAi function in a desired tissue or cell in an otherwise RNAi deficient genetic background. In a classroom setting, we attempted to assess the contribution of specific tissues t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…nas-38 is expressed prominently in the epidermis and there promotes AMP expression through STA-2 [36]. To confirm this directly, we knocked down nas-38(ok3407) with RNAi specifically in the epidermis [53]. This suppressed the increased nlp-29 expression phenotype to a similar extent as sta-2, supporting the idea that nas-38 acts in skin tissue (Figures 3I, S4H).…”
Section: Nas-38 Is Required In the Epidermis To Increase Amp Expressionsupporting
confidence: 54%
“…nas-38 is expressed prominently in the epidermis and there promotes AMP expression through STA-2 [36]. To confirm this directly, we knocked down nas-38(ok3407) with RNAi specifically in the epidermis [53]. This suppressed the increased nlp-29 expression phenotype to a similar extent as sta-2, supporting the idea that nas-38 acts in skin tissue (Figures 3I, S4H).…”
Section: Nas-38 Is Required In the Epidermis To Increase Amp Expressionsupporting
confidence: 54%
“…In contrast, pals-5 induction was less compromised by zip-1(RNAi) in the epidermal-specific RNAi strain. Because intestinal expression of rde-1 allows generation of secondary siRNAs that can spread to other tissues and silence gene expression there, we used a separate tissue-specific RNAi strain, where the sid-1 transport channel is specifically expressed in the intestine (27, 28). These mutants do not suffer from the problem of leakiness seen in the rde-1 rescue strains (28, 29).…”
Section: Resultsmentioning
confidence: 99%
“…Because intestinal expression of rde-1 allows generation of secondary siRNAs that can spread to other tissues and silence gene expression there, we used a separate tissue-specific RNAi strain, where the sid-1 transport channel is specifically expressed in the intestine (27, 28). These mutants do not suffer from the problem of leakiness seen in the rde-1 rescue strains (28, 29). However, we did note that they suffer from the opposite problem: they appear to be somewhat resistant to RNAi.…”
Section: Resultsmentioning
confidence: 99%
“…In flies, lifespan was extended by manipulation of mTORC1 pathway components using GAL4-UAS drivers primarily expressed in the fat body 8 . However, further research has shown that both tissue-specific RNAi 24 and GAL4-UAS drivers have off-target effects in other tissues 25 . In addition to being more tissue-specific than RNAi, AID has the added benefit of targeting the endogenous protein directly rather than silencing a gene at the mRNA level.…”
Section: Discussionmentioning
confidence: 99%